Strobilar Organization in Philippine Species of Selaginella - Zamora, Prescillano (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
This paper (1) describes for the first time the 12 types and subtypes of strobilar organization (based on sporophyll arrangement along the strobilar axis) found in 41 of the 50 Philippine species of SelagineIla based on the microscopic analyses of more than 2,000 cleared strobili; (2) indicates the occurrence of these types and subtypes of strobilar organization in the various species; (3) discusses the value of strobilar organization in the taxonomy of the Philippine species vis-a-vis v A v R's system of classification; and (4) proposes and presents evidence for several pathways by which the presumed most specialized derived types of strobilar organization (Type IV: one which consists wholly or predominantly of microsporophylls and Type V: one which consists wholly or predominantly of megasporophylls) could be derived from the presumed basic type (Type 1a: one with a basal zone of megasporophylls + an apical zone of microsporophylls).